Organization of Independent Education in the Credit-Module System of Teaching - Shukhratjon Turaev (Zien Journals, 2022)
The article explains that the effectiveness of education in the credit-module system of education depends on the proper organization of independent learning of students, and provides specific recommendations for the use of innovative methods in this process. While students are free to pursue a particular program in their independent study, it is important that the teacher provides the students with information on the subject, motivates them, and monitors their activities
Keywords: Credit-module system; independent education; creative thinking; information age